The Concept of Islamic Education According to Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi: A Comparative Analysis of the Epistemology and Purpose of Islamic Education - Amaliatul Fitriyah; Nurul Hayati; Miftahul Jannah; Yolanda Dwintarisma Andini; Khoiriyah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
Contemporary Islamic education faces serious epistemological challenges due to the dominance of Western secular paradigms that separate knowledge from values and perpetuate the dichotomy between religious and general sciences. This condition weakens the spiritual and ethical orientation of Islamic education, which is increasingly trapped in materialistic and utilitarian goals. In response, the ideas of Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi on the Islamization of science offer an alternative paradigm. This study aims to analyze and compare their concepts of Islamic education, particularly in terms of epistemology, educational objectives, and relevance to contemporary Islamic education in Indonesia. Using a qualitative library research method with comparative discourse analysis of key works such as Islam and Secularism and Islamization of Knowledge, this study finds that al-Attas emphasizes conceptual purification through adab and purification of meaning (tashfiyah al-ma‘na) as the epistemological foundation of education. In contrast, al-Faruqi focuses on structural reconstruction of modern science by integrating revelation and scientific rationality within a monotheistic framework. Despite methodological differences, their approaches are complementary. Their synthesis produces an integrative paradigm of Islamic education oriented toward cultivating civilized individuals and promoting social transformation based on justice and benefit. These findings underscore the urgency of reformulating curriculum, pedagogy, and institutional frameworks to ensure a holistic, monotheistic, and contextually relevant Islamic education.